PENDIDIKAN KELUARGA SEBAGAI IMPLEMENTASI PLS - Anshory, Ichsan (Jurnal Bestari, 1991)
The essence of development is the process of cotinuous change to gain a better life. In this context, the development of indonesia must give the base of attention and consideration. When the goal of development is to gain a better world, the process of education may be regarded as the main medium and the basic tool. The informal education include the family education is one of education alternative held by men to catch their ideality.